T2 Mapping Magnetic Resonance Imaging Encourages an Arthroscopic Approach for Osteoid Osteoma in the Acetabulum - Shoji, Takeshi (Elsevier, 2014)
Intra-articular osteoid osteoma (OO) is uncommon, especially in the hip joint. Delayed treatment may cause early osteoarthritis; however, diagnosis and complete excision are often challenging. We describe the feasibility of the combination of T2 mapping magnetic resonance imaging evaluation and arthroscopic excision of OO in the acetabulum. A 12-year-old boy presented with a 6-month history of hip pain. An undifferentiated tumor of the medial wall of the acetabulum was suspected on radiographs and computed tomography. T2 mapping showed joint effusion, and the T2 value of the acetabular cartilage just above the tumor was significantly high. These findings suggested OO in the acetabulum. An arthroscopic excision was performed for biopsy and excision of the tumor to avoid damage to the normal cartilage and growth plate. Histologic examination confirmed the OO. At 16 months' follow-up, there was no evidence of recurrence. This is the first report to evaluate intra-articular OO by T2 mapping and to treat it arthroscopically. Arthroscopic treatment assisted by T2 mapping has excellent potential as a minimally invasive technique to enable us to approach the tumor from the area of discriminative abnormal cartilage with minimal damage to the normal cartilage and surrounding tissue.